Uma abordagem para auxiliar a correção de erros de programadores iniciantes - Jesus, Galileu Santos de (2018)
The integration of virtual learning environments integrated with other tools, such as online judges, appears as a possibility to compensate the lack of laboratory practices in face-to-face courses, to support practical activities in semi-distance, distance and MOOC’s courses, as well as supporting teachers, enabling a better monitoring of individual. However, online judges do not always provide an appropriate or understandable feedback to the student, they usually do not support the student with hints based on how to improve or achieve a valid solution. When observing groups of beginners, the same tips are presented frequently, since the students usually fail in the same point or by the same reason. This dissertation presents a proposal to support teaching-learning of computer programming, improving the online judge The Huxley by including feedback messages that are easily understood by the learners of the initial programming disciplines and guiding them through the syntax errors presented when performing a submission to the online judge. In order to evaluate this approach, a case study with undergraduate classes was also conducted. A controlled experiment, including an analysis with statistical tests confirms the hypothesis, that the approach increased the ability to correct errors, especially among students with low English proficiency that have succeeded in the initial programming discipline.